PERUBAHAN KEPRIBADIAN TOKOH DASIYAH (JENG YAH) DALAM NOVEL GADIS KRETEK KARYA RATIH KUMALA (KAJIAN PSIKOLOGI SASTRA) - Yusran Sinaro; Arju Susanto; Kurnia Rachmawati (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research discusses how the personality changes experienced by Dasiyah (Jeng Yah) in the novel Gadis Kretek by Ratih Kumala. The theory used in this study is Sigmund Freud's literary psychology. The method used in this study is qualitative descriptive. The data source is taken from the novel Gadis Kretek by Ratih Kumala, published in 2012, this novel consists of 288 pages. The results of the research obtained refer to the data analyzed in the form of quotes consisting of Phrases, sentences, and paragraphs. The purpose of this research is to show the psychological aspects of id, ego, and superego literature, as well as personality changes experienced by Dasiyah (Jeng Yah).